Hunches that matter: the role of intuitive concern in medical understanding - Jacobs, Kerrin Artemis (Frontiers in Psychology, 2025)
This conceptual analysis examines the role of intuition in medical understanding from a philosophical point of view: (1) Intuition serves an indicative function, whereby it experientially reveals that something is of importance to us, thereby enabling us to adapt and (re)evaluate situations. This results in the emergence of a distinct conative dimension. The intuitive judgments and insights about what matters also come with an urge to act on them, which is crucial for explaining the motivation for proactive prevention of harm and the promotion of well-being. (2) One specific mode of recognizing “what matters” is being intuitively concerned. Intuitive concern can be conceptualized as a process that relies on the interplay of intuitive “knowing” and deliberative thinking in clinical decision-making. (3) It can be concluded that these hunches are significant, as they indicate not only what should be taken seriously but also the necessity of achieving accuracy. The intuitive concern is an essential aspect of medical professionalism, both as a reflexive necessity and as an expression of the “art of healing.”